Overexpression of HDAC9 is associated with poor prognosis and tumor progression of breast cancer in Chinese females - Huang, Yixiang (Onco Targets Ther, 2018)
BACKGROUND: Breast cancer represents a serious health issue among females. HDAC9 has been identified as an oncogene in human cancers. This study sought to assess the prognostic value and the biologic function of HDAC9 in breast cancer patients. METHODS: Expression of HDAC9 in breast cancer tissues and cells was evaluated by quantitative real-time polymerase chain reaction. Kaplan–Meier survival analysis and Cox regression assay were conducted to explore the prognostic significance of HDAC9. Cell experiments were performed to investigate the effects of HDAC9 on the biologic behaviors of breast cancer cells. RESULTS: Expression of HDAC9 was significantly upregulated in both cancerous tissues and cells compared with the normal controls (all P<0.05). Overexpression of HDAC9 was correlated with lymph node metastasis (P=0.021) and TNM stage (P=0.004). Patients with high HDAC9 had poor overall survival compared to those with low levels of HDAC9 (log-rank P<0.05). Elevated HDAC9 was found to be an independent prognostic factor for the patients (hazard ratio=2.996, 95% CI=1.611–5.572, P=0.001). According to the cell experiments, tumor cell proliferation, migration and invasion were suppressed by knockdown of HDAC9. CONCLUSION: All data demonstrated that overexpression of HDAC9 serves as a prognostic biomarker and may be involved in the tumor progression of breast cancer.